CHAP-E: A Plan Execution Assistant for Pilots - Benton, J.; Smith, David; Kaneshige, John; Keely, Leslie; Stucky, Thomas (Proceedings of the International Conference on Automated Planning and Scheduling, 2018)
Pilots have benefited from ever-increasing and evolving automation techniques for many decades. This automation has allowed pilots to handle increasingly complex aircraft with greater safety, precision, and reduced workload. Unfortunately, it can also lead to misunderstandings and loss of situational awareness. In the face of malfunctions or unexpected events, pilots sometimes have an unclear picture of the situation and what to do next or must find and follow written procedures that do not take into account all the details of the particular situation. Pilots may also incorrectly assume the mode or state of an automated system and fail to perform certain necessary actions that they assumed the automated system would handle. To help alleviate these issues, we introduce the Cockpit Hierarchical Activity Planning and Execution CHAP-E system. CHAP-E provides pilots with intuitive graphical guidance on what actions need to be performed and when they need to be performed based on the aircraft and automation state, and projection of this state into the future. This assists pilots in both nominal and off-nominal flight situations.